PENGGUNAAN MODEL PEMBELAJARAN PAKEM DALAM MENINGKATKAN KETERAMPILAN MENULIS DASAR SUKU KATA - Anas, Azwar; Yunita, Irma (INSTRUKTUR INSTRUKTUR: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The lack of students’ interest in writing leads to a passive classroom atmosphere and results in low writing skills, which ultimately affect learning outcomes. This study aims to analyze the effect of the PAKEM model (Active, Creative, Effective, and Joyful Learning) on students’ basic syllable writing skills. The research employed a quantitative method with a Pre-Experimental Design (One Group Pretest–Posttest Design). The subjects were one class of students without a comparison group. The study was conducted at SDIT Al-Munawwar from December 2023 to May 2024. Data were collected through observation, tests, and documentation, and then analyzed using descriptive and inferential statistics, normality tests, and hypothesis testing (t-test) with the aid of Excel and SPSS V.23. The findings indicate a significant improvement in students’ writing ability after the implementation of the PAKEM model. The average pretest score of 75.48 increased to 88.10 in the posttest. Therefore, it can be concluded that the PAKEM model has a significant effect on improving the basic syllable writing skills of first-grade students in the Indonesian language subject at SDIT Al-Munawwar